Sikap dan Kepedulian Masyarakat Terhadap Objek Wisata dan Pembangunan Berkelanjutan di Bali - I Putu Putra Astawa; I Ketut Sudibia (Widya Manajemen, 2021)
Indonesia is not only rich in natural resources but because of its exotic landscape, consisting of forests, oceans and rivers that can generate extraordinary natural tourism potential. The development of tourism has two possible impacts on the local community, namely tourism will improve the welfare of the community or on the contrary, tourism will marginalize society in all fields. The activities of developing tourist objects cannot be separated from social, economic and environmental conditions. Tourism is an industry whose survival is largely determined by the merits of the environment. This research, it examines and analyzes how the attitudes and concerns of the community towards the development of tourist objects towards sustainable development. The goal is to find out how people's attitudes and concerns affect the development of tourist objects and sustainable development. This study uses an explanatory study with literature studies to identify the impact of people's attitudes and concerns towards sustainable development. Attitudes and behaviors are the formation of perceptions, so a correct perception of an object is needed. With the existence of public concern from the beginning for tourism development, it will further ensure the success and continuation of this tourism development. Continuing development for Bali considers not only the sustainability of natural resources as a basic necessity for life, but also the sustainability of cultural resources.